Obtaining gains in efficiency when water is free - Hagan, Ross E., author; Regner, Jochen, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
Improvements in on-farm water use efficiencies in the Jordan Valley have been demonstrated by a USAID project. A GTZ project is establishing water users' organizations in the Jordan Valley that demonstrate increased water distribution equity. With improved distribution equity, the demonstrated gains in efficiency should increase. Water delivery service fees or a "water price" played no role in the average 20% reduction in water use and average 5% increase in production or yield. Also, in Jordan at the time of the project neither the responsible water distribution agency nor the Ministry of Agriculture Extension Service offered assistance to farmers in on-farm water management. The key for unlocking the potential for water conservation was knowledge transfer to the farmer. On a few selected farms the benefits to be gained from improved management were demonstrated, extension information on irrigation system management was provided to farmers, and a resource of trained irrigation specialists from the Jordan Valley Authority was available to farmers.
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."